Comparison of Selection of Sea Transportation Modes To Simeulue Port - Sinaga, Shanty Katharina (KnE Social Sciences, 2021)
The islands of Simeulue and Aceh are located in the South Indian Ocean part of Aceh, and maritime transportation is vitally important to these island communities. The users of sea transportation want a quick, affordable and comfortable service, and a convenient departure schedule. However, currently the services provided fall short of these goals, with long delays, despite the high levels of competition which should encourage service improvements. This study assesses the considerations which go into customer decisions to choose between the different providers. The results show that travel was predominantly made for recreational purposes (48%) of for trade (42%). Keywords: Mode, Ferry, Pioneer Ship